2020
DOI: 10.1021/acs.jpcc.0c08267
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond Charge Separation Time Scale at Graphene Quantum Dot Surface

Abstract: Fast exciton−exciton annihilation occurring at a few 10s ps time scale possesses a potential hurdle to the successful utilization of a multiple exciton generation (MEG) process. MEG produces over 100% quantum efficiency of exciton generation and thereby a dramatic improvement in device performance. Successful implementation of MEG would require a faster charge separation than the exciton annihilation time. In this work we showed < 1 ps photoinduced electron transfer (PET) time scale at graphene quantum dot (GQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…used ∼10 ms binning time in FL trajectory studies of surfaceimmobilized NCs. 4,43,44 This implies not only that the solution-phase blinking study reports a more accurate timescale of the blinking kinetics, but also that the observed kinetics in solution are free from the undesired interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…used ∼10 ms binning time in FL trajectory studies of surfaceimmobilized NCs. 4,43,44 This implies not only that the solution-phase blinking study reports a more accurate timescale of the blinking kinetics, but also that the observed kinetics in solution are free from the undesired interactions.…”
mentioning
confidence: 99%
“…where the reciprocal of A is the number of NCs within the excitation volume, g αα = k 1 /k 2 = 1/g ββ (for ACF fitting) and g αβ = −1 (for CCF fitting), τ k is the time constant of blinking, n is the stretching exponent (0 < n < 1) accounting for the inhomogeneity of τ k , and z (= w xy /w z ) is the ratio of the transverse radius to the longitudinal radius of the excitation volume. 43,44 This model has been used previously for the fitting of FCS autocorrelations of metal chalcogenides and very recently for perovskite NCs. 3,4,48,49,62,63 The same model was used by Hof and colleagues to fit ACFs and CCF of their FLCS study of blinking caused by spermine-induced plasmid DNA condensation.…”
mentioning
confidence: 99%
“…However, it is also difficult to distinguish the transfer routes (CB→CB or trap states→CB), and can only determine the charge transfer time from Cu 1.94 S to ZnS is ~0.091 ps. To avoid mixing up of intraband relaxation kinetics with the charge transfer component, we tried to fit the ratio curve of Cu 1.94 S-ZnS to Cu 1.94 S. 70,71 However, as the signal intensity of Cu 1.94 S NCs and Cu 1.94 S-ZnS NHs are very close and the existence of laser noise, make it is difficult to analyze the ratio curve of Cu 1.94 S-ZnS to Cu 1.94 S to obtain the charge transfer dynamics characteristics. Table 1 summarizes the carrier transfer time in different NHs synthesized via CE and traditional epitaxial growth, including metal-semiconductor hybrid NCs and semiconductorsemiconductor NHs.…”
Section: Carrier Dynamics Of Cu 194 S Ncs and Cu 194 S-zns Nhsmentioning
confidence: 99%
“…For example, CdSe quantum dots attached to different-sized Au nanoparticles (NPs) show hot electron transfer as well as ultrafast electron transfer (Figure c) . Subpicosecond interfacial charge separation and slow excitonic recombination (on the order of nanoseconds) are exhibited by graphene quantum dots in the presence of an electron-rich organic molecule . Heterogeneous charge transfer efficiency in QDs connected by redox noninnocent ligands can be modulated by tuning the interdot separation, which can be achieved through substitutional changes in the ligands .…”
mentioning
confidence: 99%
“…26 Subpicosecond interfacial charge separation and slow excitonic recombination (on the order of nanoseconds) are exhibited by graphene quantum dots in the presence of an electron-rich organic molecule. 27 Heterogeneous charge transfer efficiency in QDs connected by redox noninnocent ligands can be modulated by tuning the interdot separation, which can be achieved through substitutional changes in the ligands. 28 Passivation of QDs with organic molecules affects the energy gap and electron−vibrational interactions, and it can favor charge separation and suppress charge recombination.…”
mentioning
confidence: 99%